PELATIHAN PEMBUATAN SNACK DARI DAUN PEPAYA JEPANG UNTUK MEWUJUDKAN LANSIA “SEHATI” (SEHAT DAN PRODUKTIF) - Ayu Susanti, Dhina; Rian Anggia Destiawan (LPPM Universitas dr. Soebandi, 2025)
Elderly people must maintain a healthy diet because they are very susceptible to disease. Therefore, education is needed about the importance of consuming healthy food and assistance in processing healthy food to realize SEHATI (Healthy and Productive) elderly people. There are many natural ingredients around the yard that can be processed into healthy dishes for the elderly. Japanese papaya leaves are widely planted in yards and are rarely used. Japanese papaya leaves contain flavonoids, alkaloids, tannins and saponins which are very useful as antioxidants and immunomodulators. This activity was carried out through counseling and practice of making healthy snacks with Japanese papaya leaves as the basic ingredient for 23 elderly people who participated in the SELANTANG (Sekolah Lansia Tangguh) Jember activity which took place at the Griya Mangli Housing Complex, Jember. The purpose of this PkM activity is for participants to better understand the importance of elderly health and to equip them with skills in making healthy snacks that can be consumed with family or sold to increase the economy so that they can contribute to realizing the elderly